2016
DOI: 10.1002/asna.201612384
|View full text |Cite
|
Sign up to set email alerts
|

Non‐LTE iron abundances in cool stars: The role of hydrogen collisions

Abstract: In the aim of determining accurate iron abundances in stars, this work is meant to empirically calibrate H-collision cross-sections with iron, where no quantum mechanical calculations have been published yet. Thus, a new iron model atom has been developed, which includes hydrogen collisions for excitation, ionization and charge transfer processes. We show that collisions with hydrogen leading to charge transfer are important for an accurate non-LTE modeling. We apply our calculations on several benchmark stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The temperature and microturbulent velocity of J0937−0626 were determined by removing trends in the NLTE Fe I abundances with wavelength, reduced EW, and excitation potential (see Figure 1); the surface gravity was found by forcing agreement between NLTE Fe I and Fe II abundances. The final adopted parameters are listed in Table 1, along with the LTE parameters and the parameters derived with the 1D NLTE corrections of Ezzeddine et al (2017, also see Ezzeddine et al 2016 andSakari et al 2018b Schuster et al (2004) and Beers et al (2007) obtained photometry of J0937−0626, finding colors that are consistent with the spectroscopic parameters derived here. Schuster et al (2004) classified J0937−0626 as a "red-horizontal-branch-asymptotic-giant-branch transition" star, while Beers et al (2007) found that it was displaced from the metal-poor main sequence, potentially as a result of its lower surface gravity.…”
Section: Introductionsupporting
confidence: 76%
“…The temperature and microturbulent velocity of J0937−0626 were determined by removing trends in the NLTE Fe I abundances with wavelength, reduced EW, and excitation potential (see Figure 1); the surface gravity was found by forcing agreement between NLTE Fe I and Fe II abundances. The final adopted parameters are listed in Table 1, along with the LTE parameters and the parameters derived with the 1D NLTE corrections of Ezzeddine et al (2017, also see Ezzeddine et al 2016 andSakari et al 2018b Schuster et al (2004) and Beers et al (2007) obtained photometry of J0937−0626, finding colors that are consistent with the spectroscopic parameters derived here. Schuster et al (2004) classified J0937−0626 as a "red-horizontal-branch-asymptotic-giant-branch transition" star, while Beers et al (2007) found that it was displaced from the metal-poor main sequence, potentially as a result of its lower surface gravity.…”
Section: Introductionsupporting
confidence: 76%
“…However, unlike what is expected for an intrinsic atomic property, different S H were obtained by different studies which were found to be star and model atom dependent (e.g. Thévenin & Idiart 1999;Korn et al 2003;Mashonkina et al 2016;Bergemann et al 2012;Ezzeddine et al 2016a).…”
Section: Introductionmentioning
confidence: 79%
“…We thus also determine NLTE stellar parameters using a complete iron model atom introduced in Ezzeddine et al (2016). For inelastic hydrogen collisions, we use quantum-based rates inspired by fitting quantum rates of Na, Mg, Al, and Si and applying them to Fe (R. Ezzeddine et al 2016, in preparation).…”
Section: Observations and Abundance Analysismentioning
confidence: 99%